Effects of 25 mg oxazepam on emotional mimicry and empathy for pain: a randomized controlled experiment. Issue 3 (8th March 2017) - Nilsonne, Gustav; Tamm, Sandra; Golkar, Armita; Sörman, Karolina; Howner, Katarina; Kristiansson, Marianne; Olsson, Andreas; Ingvar, Martin; Petrovic, Predrag
Abstract : Emotional mimicry and empathy are mechanisms underlying social interaction. Benzodiazepines have been proposed to inhibit empathy and promote antisocial behaviour. First, we aimed to investigate the effects of oxazepam on emotional mimicry and empathy for pain, and second, we aimed to investigate the association of personality traits to emotional mimicry and empathy. Participants ( n =76) were randomized to 25 mg oxazepam or placebo. Emotional mimicry was examined using video clips with emotional expressions. Empathy was investigated by pain stimulating the participant and a confederate. We recorded self-rated experience, activity in major zygomatic and superciliary corrugator muscles, skin conductance, and heart rate. In the mimicry experiment, oxazepam inhibited corrugator activity. In the empathy experiment, oxazepam caused increased self-rated unpleasantness and skin conductance. However, oxazepam specifically inhibited neither emotional mimicry nor empathy for pain. Responses in both experiments were associated with self-rated empathic, psychopathic and alexithymic traits. The present results do not support a specific effect of 25 mg oxazepam on emotional mimicry or empathy.